(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The Complaint Management System (CMS) research paper presents a comprehensive solution to address the challenges organizations face in managing customer complaints. By developing an efficient and user-friendly framework, the CMS aims to streamline the entire complaint resolution process. Through a centralized platform, customers can easily submit complaints and track their progress, ensuring timely resolution and enhancing overall satisfaction. The system's web-based interface facilitates seamless communication between customers and support staff, with features such as real-time updates and a dashboard displaying all incoming complaints. Additionally, the CMS incorporates advanced data analysis capabilities, enabling organizations to identify recurring issues and trends, thus empowering them to implement proactive measures for improvement. By leveraging technology to enhance customer support processes, the CMS research paper seeks to revolutionize the way organizations handle complaints, ultimately leading to improved customer experiences and loyalty.